Estrutura fina do espermatozóide de Tagelus plebeius (Lightfoot) (Mollusca, Bivalvia) do litoral norte do Brasil - MATOS, Edilson Rodrigues (2014)
It is described the sperm ultraestructure differentiation during spermiogenesis of Tagelus plebeius (Lightfoot, 1786). The spermatozoon is an uniflagellated cell of the primitive type. The head region contains a rounded or conical nucleus surrounded by acrosome. The middle piece contains four mitochondria which are arranged around the axoneme. The flagellum contains the usual microtubular axoneme.